GROWTH HISTORY OF SHALLOW-WATER CARBONATES: CONTROL OF ACCOMMODATION ON ECOLOGICAL AND DEPOSITIONAL PROCESSES - Masse J.P.; Montaggioni L.F. (My University, 2001)
We explore the role played on the growth of shallow-water carbonates by changes in accommodation using case studies from Late Quaternary to modern carbonate environments, i.e. coral reefs and carbonate platforms and ramps. Accommodation appears not to influence either primary productivity or community structure (K- versus r-strategists) as these are directly governed by nutrient supply; but it does control submarine depositional profiles and their stratigraphic expression (i.e. volumetric sedimentary partitioning). The growth of communities from incipient to senescent stages is dictated by relative rates of sea-level variations, although ambient temperatures and trophic conditions may modify the community response. A decrease or stabilization of accommodation favours lateral migration, thus generating ecological and sedimentary innovations. Organic carbon production tends to be positively correlated to that of carbonate, both declining as accommodation decreases. Shallow water carbonates develop as a result of the interplay of factors, including the types and rates of biological and physical processes. Applying depositional models of Recent shallow-water carbonates to the interpretation of ancient carbonate platforms first needs to acknowledge the respective role of the two contrasting phases that operated during the post-glacial sea-level rise (an earlier, fast-rising phase versus a later, slowly rising to stabilizing phase); the period of relative sea-level stabilization (i.e. the past 6,000 years) appears a relevant reference for still-stand-related carbonate systems. Furthermore, the oligotrophic nutrient model, a dominant feature of the modern shallow-water tropics, can be used as an analogue in reconstructing carbonate growth histories during greenhouse episodes of Earth history.
Keywords: ACCOMMODATION; BENTHIC COMMUNITIES; CARBONATE PLATFORMS AND REEFS; PRODUCTION OF ORGANIC CARBON AND CARBONATE; RECENT SEDIMENTARY SYSTEMS; Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная